The Effect of Teaching Reading Strategies on the Students’ Motivation to Read in English - MEZHOUD, Sorya (Journal of Human Sciences, 2015)
The present study aims at investigating the effect of teaching reading strategies to non motivated readers on their motivation to read in English. It is based on the hypothesis that some students lack motivation to read in English due to their employment of inadequate reading strategies, and that if they are trained in the use of more effective ones, then this motivation will subsequently increase. To test these hypotheses, a first questionnaire is administered to all first year students of English at the Teacher Training School of Constantine in order to identify the non motivated ones and the cause(s) of this lack of motivation. Instruction on more effective reading strategies is then provided to fourteen students among the non motivated ones. At the end of this instruction, a second questionnaire is administered to these students to determine its success in enhancing their motivation to read in English.